"V tvoji luči vidimo luč." (Ps 36,10) - Palmisano, Maria Carmela (Bogoslovni vestnik, 2025)
In Ps 36:10b, the vision of God's light is presented as a vision and spiritual experience of a group that exclaims and speaks to God in the second person: “In your light we see light.” The article presents the rich symbolism of “water” and “light” in v. 10 and in the broader literary context of Ps 36, based on the Hebrew original and Hebrew poetry, considering old translations as well. Water and light in the psalm represent the essence of life that originates from God. Furthermore, the article demonstrates the significance of the tripartite structure of the psalm (vv. 2-5.6-10.11-13), which outlines the vision of the wicked, the vision of God in the center of the poetic composition, and the twofold petition of the worshiper at the end. The article analyzes the particular features of each part of the composition from an exegetical theological point of view and presents an interpretation of the entire psalm as a deep understanding of history in the light of God, which goes beyond any attempt to connect the psalm to a specific historical context. This is acknowledged by most commentators. The article interprets the psalm in light of Jewish-Christian tradition. The final section connects the theological message of the psalm with the work of the Jewish painter, Marc Chagall, “White Crucifixion” (1938) and his profound reflection on the mystery of history and suffering in light of the crucifixion of Christ.
Keywords: Christian interpretation; drink; eschatology; eshatologija; faithfulness; food; history; hrana; images; izvir; Jewish interpretation; judgment; judovska interpretacija; krivičnik; krščanska interpretacija; light; luč; Marc Chagall, “White Crucifixion”; Marc Chagall, „Križanje v belem“; pijača; podobe; pravičnost; Ps 36; righteousness; simbolika; sodba; spring; symbolism; tempelj; temple; the wicked; voda; water; zgodovina; zvestoba